Application of direct MRAC in PI controller for DC-DC boost converter - Lunde Ardhenta; Ramadhani Kurniawan Subroto (Institute of Advanced Engineering and Science, 2020)
Almost all electronic components require a DC power supply at present days. The needs of DC power supplies from low voltage scales, medium voltages such as generators, to high voltage scales for high voltage electricity transmission. The improvement of PI controller performances is presented in this paper. The adaptation gains improve transient response of DC-DC Boost Converter several operating conditions. Massachusetts Institute of Technology (MIT) rule is applied as an adaptive mechanism to determine the optimal control parameters in some conditions. The used adaptive control technique is Direct Model Reference Adaptive Control (MRAC), this method as able to control system in some various input voltage. The proposed method has a stable response and able to reach the model reference smoothly. However, the response of the system has instantaneously overshoot and follows the response back of model reference. The responses of proposed controller have short period of rise time, settling time, and overshoot.